Rural development strategy the experience of India [review of] - Mariano, Vicente D. (1989)
A review of R.C. Mascarenhas, A Strategy for Rural Development (New Delhi/Newbury/Park London: Sage Publications, 1988), 295 pages.
Keywords: Book reviews; Rural development